PEMANFAATAN LIMBAH POTONGAN KAYU UNTUK PEMBUATAN MAINAN EDUKATIF “BOARD GAMES SI KIKO” - Ardana Putri Farahdiansari; Moh Nurudduja (Cv. Utility Project Solution, 2023)
Bojonegoro is one of the areas that has a lot of woodcraft industries, precisely in the Sukorejo area. From these woodcraft industries there are many small pieces of wood that have not been utilized. One type of waste generated from activities in the wood industry is in the form of wood chips of 9.39% with a width of 10-25 cm, a thickness of 2-3 cm and a length of 3-12 cm. Industrial Engineering in Bojonegoro University took the initiative to utilize these pieces of wood waste as a product design process practice while at the same time producing useful product outcomes. Using machines in Manufacturing Lab, the community service that is being carried out is to turn this wood waste into an educational toy for children which is named the SI KIKO Board Games. Processing of wood waste will provide good benefits for student activities in the Manufacturing Lab and also contribute to reducing environmental waste and contributing to the world of early childhood education.